MANAGING IC IN AN OPERA HOUSE: THE CASE OF LA SCALA - Pierotti, Mariarita; Risaliti, Gianluca; Cestari, Greta (European Scientific Journal, ESJ, 2014)
In this paper we refer to IC as the dynamic and firm-specific system of intangible resources and activities based on knowledge, which, interacting with tangible resources, is able to generate competitive sustainable advantages, at the basis of the firm’s performance variations. We strongly believe that IC can provide a conceptual framework for managing Non-Profit Organizations (NPO), as their main inputs and outputs are intangible in nature. Inside the No – Profit area, extremely diversified sector, are traditionally included the cultural companies. These realities are themselves characterized by a great variety of typologies: museums, theatres, record labels, television companies, radio stations etc. In particular, validating the articulation of IC into the three subcategories of human capital, organizational capital and relational capital, we has the aim to decline these subcategories for the Opera Houses, underlining the specificities of the cultural organizations. In this contribution, starting from the above defined dimensions of IC we propose to understand if, in the case of the Teatroalla Scala, the Human Capital and the Relational Capital are managed “by antennae” (Donato, 2008). Furthermore we will deepen a possible evolutionary path of the measurement instruments and the model of Intellectual Capital Reporting that can be proposed to the managers of the theatre.